2014
DOI: 10.1182/blood.v124.21.3118.3118
|View full text |Cite
|
Sign up to set email alerts
|

Three BTK-Specific Inhibitors, in Contrast to Ibrutinib, Do Not Antagonize Rituximab-Dependent NK-Cell Mediated Cytotoxicity

Abstract: Introduction: The BTK inhibitor, ibrutinib is FDA-approved in MCL and CLL, with activity in the majority of CD20+ B-cell malignancies. As rituximab-combination chemotherapy is today's standard of care in CD20+ B-cell malignancies, we previously investigated and determined ibrutinib antagonizes rituximab-dependent NK-cell mediated cytotoxicity (ADCC) due to ibrutinib's secondary irreversible binding to interleukin-2 inducible tyrosine kinase (ITK) which is required for FcR-stimulated NK cell function including … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
16
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 0 publications
2
16
0
Order By: Relevance
“…Ibrutinib resulted in decreased phosphorylation at tyrosine 180 (Y180) of ITK, confirming ITK as a known target of ibrutinib (Fig C) (Dubovsky et al , ). These data are consistent with previous reports indicating that ibrutinib antagonized rituximab‐dependent NK cell‐mediated cytotoxicity (Kohrt et al , ; Rajasekaran et al , ; Roit et al , ), however one group has demonstrated that ibrutinib increased NK cell‐mediated activity of mouse NK cells (Kuo et al , ).…”
Section: Resultssupporting
confidence: 92%
“…Ibrutinib resulted in decreased phosphorylation at tyrosine 180 (Y180) of ITK, confirming ITK as a known target of ibrutinib (Fig C) (Dubovsky et al , ). These data are consistent with previous reports indicating that ibrutinib antagonized rituximab‐dependent NK cell‐mediated cytotoxicity (Kohrt et al , ; Rajasekaran et al , ; Roit et al , ), however one group has demonstrated that ibrutinib increased NK cell‐mediated activity of mouse NK cells (Kuo et al , ).…”
Section: Resultssupporting
confidence: 92%
“…ITK is also expressed in natural killer (NK) cells (Khurana et al, 2007), and inhibition thereof has been reported to decrease the antibody-dependent cellular cytotoxicity function of NK cells (Kohrt et al, 2014). It was reported that ibrutinib inhibited both rituximab-and trastuzumab-induced NK cell cytokine secretion and lysis in vitro in a dose-dependent manner (0.1 and 1 mM), whereas acalabrutinib did not show any effects at 1 mM (Rajasekaran et al, 2014). This indicates that acalabrutinib is associated with a reduced risk of affecting antibody-dependent cellular cytotoxicity-mediated therapies.…”
Section: Discussionmentioning
confidence: 99%
“…The emergence of ibrutinib-resistant disease and subsequent studies have uncovered potential contributors to ibrutinib resistance in MCL, including acquired BTK mutations that interfere with ibrutinib binding or aberrant upregulation of PI3K (12,13). Assessment of novel BTK inhibitors therefore provides a valuable platform to study BTK as a rational therapeutic target and to probe the role of BTK in ibrutinib resistance.…”
Section: Introductionmentioning
confidence: 99%